2021
DOI: 10.3389/fmicb.2021.771617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Zinc Sources on Growth Performance and Gut Health of Weaned Piglets

Abstract: The present study aimed to investigate the effects of dietary zinc sources on the growth performance and gut health of weaned piglets. In total, 96 Duroc × Landrace × Yorkshire (DLY) weaned piglets with an initial average body weight of 8.81±0.42kg were divided into four groups, with six replicates per treatment and four pigs per replicate. The dietary treatment groups were as follows: (1) control group, basal diet; (2) zinc sulphate (ZnSO4) group, basal diet +100mg/kg ZnSO4; (3) glycine zinc (Gly-Zn) group, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 57 publications
5
28
2
1
Order By: Relevance
“…When comparing different zinc sources, it was found that the bioavailability of organic zinc sources was relatively higher than that of inorganic zinc ( 8 ). In the present study, the final BW and ADG of pigs in the ZnMet group were higher than that in the ZnSO 4 group, indicating a beneficial effect of amino acid-chelated zinc on growth performance and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When comparing different zinc sources, it was found that the bioavailability of organic zinc sources was relatively higher than that of inorganic zinc ( 8 ). In the present study, the final BW and ADG of pigs in the ZnMet group were higher than that in the ZnSO 4 group, indicating a beneficial effect of amino acid-chelated zinc on growth performance and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the deficiency of zinc could cause numerous metabolic disorders, such as oxidative stress or immune system-related diseases, and may even increase COVID-19 infectious risk ( 5 7 ). In recent years, zinc sources have experienced the development process from inorganic zinc to organic zinc form, including amino acid-chelated zinc ( 8 ). Among them, several studies have shown that amino acid-chelated zinc has higher biological efficacy, utilization rate, and better stability, which could improve growth performance and reduce environmental pollution ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ZIPs increase the intracellular Zn concentrations by Zn import, and ZnTs reduce cytoplasmic Zn concentrations by Zn export (Bin et al, 2018). Some previous studies indicated that Zn transport proteins might also participate in the absorption of Zn as organic Zn sources in the small intestine (He et al, 2019;Diao et al, 2021). He et al (2019) reported that organic Zn increased the mRNA expression of Zn transporter 1 (ZnT1) in the jejunum of broilers challenged with Eimeria maxima and Clostridium perfringens.…”
Section: Introductionmentioning
confidence: 99%